A human-centered blended learning model for curriculum reconstruction in the industry 5.0 era - Arif, Miftakhul (Education and Social Sciences Review, 2025)
The emergence of Industry 5.0 presents new demands for curriculum models that are not only technologically adaptive but also human-centered. This article proposes a conceptual model for curriculum reconstruction based on blended learning, combining digital and face-to-face modalities to promote flexibility, personalization, and deeper engagement. Positioned as a strategic response to the pedagogical and ethical challenges of Industry 5.0, the model integrates interdisciplinary content, learner autonomy, and authentic assessment practices. Findings suggest that blended learning, when designed as a core curricular architecture rather than a delivery method, enables the formation of future-ready learners. It is concluded that integrating blended learning into curriculum frameworks is essential for creating inclusive and resilient education systems, and institutions are encouraged to adopt this model as a foundation for long-term transformation